The Dilemmas in Theories of Economic Growth versus Oded Galor's Unified Theory - Malaga , Krzysztof (Studia Oeconomica Posnaniensia, 2026)
The problems of economic growth and development, such as real economic mechanisms and processes, are still at the center of analysis and theoretical reflections of contemporary economists. This work serves to identify the cognitive boundaries that have primarily methodological nature. In this article we present ten dilemmas of contemporary theory of economic growth, two classifications of contemporary theories of economic growth, as well as the fundamental elements and achievements of the unifi ed growth theory by O. Galor [2011]. The major objective of this contribution is to confront O. Galor's unifi ed growth theory with the major dilemmas of the theories of economic growth.